Isolation and Characterization of Gallic Acid, Quercetin and Methyl Dehydrochebulate from Phyllanthus niruri (Dukung Anak) - A, Ahmeda,; (Zhari Ismail), Ismail Z. (Malaysian Journal of Science, 2005)
Three natural compounds, gallic acid, methyl dehydrochebulate and quercetin were isolated from the methanolic extract of the leaves of Phyllanthus niruri. All the isolated compounds were identified on the basis of ¹UV, IR, IH NMR, ¹³C NMR, mass spectra and elemental analysis